2007
DOI: 10.1111/j.1532-849x.2007.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress Distribution after Installation of Fixed Frameworks with Marginal Gaps over Angled and Parallel Implants: A Photoelastic Analysis

Abstract: Stresses were generated after screw tightening of the frameworks, increasing when a load was applied and when a vertical gap was present. Angled implants resulted in oblique stress patterns, which were not transferred with homogeneity to the polymeric model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
49

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 6 publications
1
42
1
49
Order By: Relevance
“…16,17 This method has been widely applied in dentistry by allowing direct observation of the stress distribution in structures due to the ability of some colorless materials to generate color patterns known as isochromatic fringes during loading and observed in polarized light. 18,19,20,21 One limitation of this technique is the reproducibility of the physical characteristics of the peri-implant tissues, since the photoelastic model has Table 1. Shear stress mean to the two groups in three loads simulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 This method has been widely applied in dentistry by allowing direct observation of the stress distribution in structures due to the ability of some colorless materials to generate color patterns known as isochromatic fringes during loading and observed in polarized light. 18,19,20,21 One limitation of this technique is the reproducibility of the physical characteristics of the peri-implant tissues, since the photoelastic model has Table 1. Shear stress mean to the two groups in three loads simulation.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,20 The models were analyzed from two sides (left and right). Qualitative analysis of the stress distribution was made using images obtained from circular polariscope.…”
Section: Photoelastic Analysismentioning
confidence: 99%
“…Other studies reported in literature have also evaluated the influence of dental implant design (Figure 2) [39] as also normal dentition, in the load mechanism transfer between teeth or dental prostheses to the surrounding bone [40,41] and also related to the method of retention of dental prostheses to abutments [42][43][44]. The influence of gap values between a fixed framework and implants, placed parallel or angled, in the stress distribution was also investigated [45]. Figure 2.…”
Section: Dental Applicationsmentioning
confidence: 99%
“…Alguns fatores foram observados na literatura focando a participação do tipo de prótese, do material utilizado (Suedam et al, 2009), da adaptação das mesmas (Binon et al, 1994;Millington;Leung, 1995;Markarian et al, 2007), tipo de conexão (Cehreli et al, 2004;Bernardes et al, 2007;Canay;Nishioka et al, 2009), da altura e diâmetro dos componentes (Suedam et al, 2009). …”
Section: Discussionunclassified
“…As variações e seus efeitos são amplamente discutidas (Schenk;Buser, 1998;Romanos;Nentwig, 2000). (Suedam et al, 2009), da adaptação das mesmas (Binon et al, 1994;Millington;Leung 1995;Markarian et al, 2007), tipo de conexão (Cehrieli et al, 2004;Bernardes et al, 2007;Canay;Nishioka et al, 2009), da altura e diâmetro dos componentes (Suedam et al, 2009 Outros estudos comprovam que a distribuição das tensões não é alterada segundo tipo de conexão protética, principalmente quando o torque correto é aplicado (Bernardes et al, 2007).…”
Section: Desenho Dos Implantes E Conexões Protéticasunclassified